Aksjologiczny wymiar rozstrzygnięć w teorii i praktyce resocjalizacji - Sztuka, Mariusz (Horyzonty Wychowania, 2017)
The author touches upon the issues of contemporary conditions of rehabilitation activity from the perspective of changes taking place in the sphere of rehabilitation teleology, as well as transformations concerning phenomena of social pathology. Along with the progress observed in the area of the ability to explain the basis and nature of deviation behaviours in a rational way, the model of a deviant expressed mainly in moral or religious terms is suffering from erosion. Simultaneously, a perceptible increase in the size of social pathology and the disturbing changes in its nature in the perspective of the previous decades, which is perceived as a fragment of a more general crisis of values, gives rise to the necessity of an urgent intervention of preventive and corrective kind. These circumstances result in a difficulty, which signals its presence on the level of concrete educational decisions, and also emphasizes certain constant ambivalences constituting the professional role of rehabilitation pedagogue.